KONTRIBUSI INFORMASI TENTANG SMK TERHADAP MINAT SISWA SMP DAN MTs MELANJUTKAN STUDI KE SMK - 155-161 . M.Arif (Universitas Negeri Padang, 2013)
This research aimed to determine the contribution of information aboutvocational high schoolon interests of studentsin Junior schooltocontinue their studies to vocational high school. This studyis a correlational study, thepopulationis all students in gradeIXJunior schoolinPayakumbuh. Technique Clusterproportionalrandom sampling used to take sample. The instrument of this research is the form ofa questionnaireto be testedpriorto thevalidity andreliability of the instrument. Analysis ofthe datausing parametricstatisticalcorrelationsviaa computer izedprogram SPSS version 15.00 atsignificance levelα=0.05. The study statesthat1) In mostclass IX students Payakumbu hobtain information about vocational high school well. 2) In mostclass IX student interest Payakumbu hal ready wellinto the vocational high school well. 3) There is asignificant contribution totheinformationaboutvocationalhigh school on interestclass IXstudent junior high school as Payakumbuhto entervocational school. Key words : Interest, Student of SMP / MTs Level, Student of SMK Level